The relationship between the climate of organizations and the type of communication in a public institution - Sandu, Mihaela Luminița; Tasențe, Tănase; Stafie, Georgiana Mădălina (Technium Social Sciences Journal, 2021)
The organizational climate is a multi-dimensional construction that comprises a variety of work environment assessments. These assessments may refer to the dimensions of the environment, such as roles within the institution, load orientation and most often communication. The overall perceptions of the organizational climate develop as individuals attribute meaning to their organizational context based on the significance of the balance of work environment and individual values. The organizational climate fully in line with the type of effective communication dominates the public institutions in Romania, contributing to administrative efficiency.